Perceptions about Entrepreneurship in the COVID-19 Era - García Lirios, Cruz; Juárez Nájera, Francisco; Bustos Aguayo, José Marcos; Juárez Nájera, Margarita; Juárez Nájera, Francisco Rubén (Razón Crítica, 2022)
This work sought to specify a model for the study of the coffee-growing sector. A cross-sectional and exploratory research with a non-random selection of 100 coffee traders was carried out. From a structural model reliability and validity, five dimensional perceptions of economic, financial, sales, social, and environmental opportunity were identified. Based on the theoretical and conceptual frameworks, we propose to study the entrepreneurial perceptions of vulnerable groups dedicated to the trading of coffee byproducts as a subsistence means. The findings allow us to establish a link between rational choice theory and the theory of human capital with respect to the theory of the commons and the theory of social entrepreneurship as conceptual frameworks to highlight the intervention in microfinance made with entrepreneurs.